An Analysis of Dental Fricative Sound’s Production: Case Study of 5th Semester Students of UIN Sjech M. Djamil Djambek Bukittinggi) - Hasan, Ibrahim; Sakti, Genta; Reflinda, Reflinda; Syahrul, Syahrul (Ability: Journal of Education and Social Analysis, 2024)
This research was motivated by the problems of students of the English education study program at UIN Sjech M. Djamil Djambek Bukittinggi. Some students pronounce the dental fricative sound in various ways. First, some students pronounce the sound /?/ correctly, however, there are also some students pronounce the sound /?/ by replacing it with the sound /t/. Second, some students pronounce the sound /ð/ correctly, however, there are also some students pronounce the sound /ð/ by replacing it with the sound /d/. The researcher's question in this study was how students pronounce the dental fricatives sound at the initial, medial and final position of a word based on the PRAAT application. The purpose of this study was to analyze the way students pronounce the dental fricative sound at the initial, middle and final of a word based on the PRAAT application. This study uses a qualitative research method with seventh semester students as the research population. The research sample amounted to 13. Data was collected through audio recordings. Students are asked to pronounce 12 words that contain the sound of dental fricative sound. The sound is uploaded to the PRAAT software. The results showed that some of the students pronounce the dental fricative sound correctly, showed by a spectogram display like a scribble pattern in the focus phoneme. others pronounce the dental fricative sound incorrectly, showed by an empty area on spectrogram in the focus phoneme. It showed that they replaced the phoneme with another phoneme such as /t/ or /d/. Researchers can conclude as follows. First, some students pronounce the dental fricative sound correctly. Second, most of the students pronounce the dental fricative sound incorrectly.